Age significantly influences the sensitivity of SARS-CoV-2 rapid antibody assays. (August 2021) - Irwin, Natalie; Murray, Lyle; Ozynski, Benjamin; Richards, Guy A; Paget, Graham; Venturas, Jacqueline; Kalla, Ismail; Diana, Nina; Mahomed, Adam; Zamparini, Jarrod
HIGHLIGHTS: Rapid tests in resource-scarce settings are a promising tool in COVID-19 diagnosis Antibody testing was conducted on people with previous COVID-19 diagnoses, using five rapid assays Overall sensitivity to SARS-CoV-2-specific antibodies was below 70% in all assays Sensitivity was reduced for those under 40 compared with those over 40 years of age Gender, disease severity, and time since test did not have an effect on sensitivity ABSTRACT: BACKGROUND: Point-of-care serological assays are a promising tool in COVID-19 diagnostics but do have limitations. Our study evaluated the sensitivity of five rapid antibody assays and explored factors influencing their sensitivity in detecting SARS-CoV-2-specific IgG and IgM antibodies. METHODS: Finger-prick blood samples from 102 participants, within 2–6 weeks of PCR-confirmed COVID-19 diagnosis, were tested for IgG and IgM using five rapid serological assays. The assay sensitivities were compared, and patient factors evaluated in order to investigate potential associations with assay sensitivity. RESULTS: Sensitivity ranged from 36% to 69% for IgG and 13% to 67% for IgM. Age was the only factor significantly influencing the likelihood of a detectable IgG or IgM response. Individuals aged 40 years and older had an increased likelihood of a detectable IgG or IgM antibody response by rapid antibody assay. CONCLUSION: Rapid serological assays demonstrate significant variability when used in a real-world clinical context. There may be limitations in their use for COVID-19 diagnosis among the young.